Germline SDHB‐inactivating mutation in gastric spindle cell sarcoma. Issue 10 (26th June 2020) - Heilig, Christoph E.; Horak, Peter; Lipka, Daniel B.; Mock, Andreas; Uhrig, Sebastian; Kreutzfeldt, Simon; Richter, Susan; Gieldon, Laura; Fröhlich, Martina; Hutter, Barbara; Hübschmann, Daniel; Teleanu, Veronica; et al.
Abstract: Gastrointestinal stromal tumors (GISTs) are the most frequent mesenchymal tumors of the gastrointestinal tract. Inactivating mutations or epigenetic deregulation of succinate dehydrogenase complex ( SDH ) genes are considered defining features of a subset of GIST occurring in the stomach. Based on comprehensive molecular profiling and biochemical analysis within a precision oncology program, we identified hallmarks of SDH deficiency (germline SDHB ‐inactivating mutation accompanied by somatic loss of heterozygosity, lack of SDHB expression, global DNA hypermethylation, and elevated succinate/fumarate ratio) in a 40‐year‐old woman with undifferentiated gastric spindle cell sarcoma that did not meet the diagnostic criteria for other mesenchymal tumors of the stomach, including GIST. These data reveal that the loss of SDH function can be involved in the pathogenesis of non‐GIST sarcoma of the gastrointestinal tract.